Red, Black and Blues: Race, Nation and Recognition for the Bluez - Cain, M. Celia (MUSICultures, 2006)
For centuries, the First Nations have been systematically disenfranchised from their lands and denied their place both in North American cultural history and contemporary culture. This article explores recent attempts to recognize First Nations music as the roots of North American popular music, specifically the blues, while considering the role of race and ethnicity in the rise of the Rez Bluez genre in Canada and the United States.